1989
DOI: 10.1136/bjo.73.6.463
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pigmented paravenous retinochoroidal atrophy.

Abstract: SUMMARY A 47-year-old Japanese man had a progressive degeneration of the retina and choroid along the retinal veins associated with uveitis of two years' duration. The lesion was characteristic of paravenous retinochoroidal atrophy: a contiguous atrophy of the retinal pigment epithelium and choroid of one-half to one disc diameter in size was present along most of the veins from the posterior pole to the far periphery. Fluorescein angiography showed a window defect in the retinal pigment epithelium, with hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Yamaguchi et al reported a 47-year-old Japanese man who had a progressive degeneration of the retina and choroid along the retinal veins associated with uveitis of 2 years' duration. 10 Haustrate and Osterhuis reported five patients with PPRA and in one patient they observed signs of active uveitis and progression of fundus lesions. 3 Macular involvement is very rare in this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamaguchi et al reported a 47-year-old Japanese man who had a progressive degeneration of the retina and choroid along the retinal veins associated with uveitis of 2 years' duration. 10 Haustrate and Osterhuis reported five patients with PPRA and in one patient they observed signs of active uveitis and progression of fundus lesions. 3 Macular involvement is very rare in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is generally bilateral and young adults are most commonly affected. The cause of the disease is unknown although an inflammatory 10 or hereditary 11 aetiology has been suggested. We report a case with typical fundus appearance of paravenous pigmented retinochoroidal atrophy accompanied by an active inflammation with cystoid macular edema.…”
mentioning
confidence: 99%
“…The final appearance was probably the result of postinflammatory scarring. The condition has been described as both progressive and nonprogressive in both children and the elderly by different authors [9, 10, 11, 12, 13]. In most cases, the optic nerve, the unaffected retina and the caliber of the retinal vessels are normal.…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge there have been two reports of active inflammation with disease [7, 9]. The natural course of PPRCA has been considered controversially [10].…”
Section: Discussionmentioning
confidence: 99%
“…Different etiologies have been discussed for PPRCA in man, including an inflammatory pathogenesis caused by tuberculosis, syphilis, sarcoidosis, or measles virus,[ 12,15 ] and genetic defects 13,16–18 . For the latter, an association with the crumbs homolog 1 encoding gene (mutations in this gene are associated with Leber congenital amaurosis and with a severe form of retinitis pigmentosa in man) that is expressed in the inner segments of the photoreceptors has been made.…”
Section: Discussionmentioning
confidence: 99%